(x 2 + 4x + 8)(2x - 1)

Question

Asked 5/1/2015 11:13:04 AM

Updated 5/14/2015 12:49:31 PM

1 Answer/Comment

Flagged by yeswey [5/14/2015 12:49:31 PM]

s

Question

Asked 5/1/2015 11:13:04 AM

Updated 5/14/2015 12:49:31 PM

1 Answer/Comment

Flagged by yeswey [5/14/2015 12:49:31 PM]

Rating

3

(x^2 + 4x + 8)(2x - 1)

= 2x^3 - x^2 + 8x^2 - 4x + 16x - 8

= 2x^3 + 7x^2 + 12x - 8

= 2x^3 - x^2 + 8x^2 - 4x + 16x - 8

= 2x^3 + 7x^2 + 12x - 8

Added 5/14/2015 12:49:29 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/16/2015 1:43:19 AM]

Simplify 8 + 3{x - 2[x + 5(x + 3)]}.

Question

Not Answered

Updated 4/24/2015 7:00:12 PM

1 Answer/Comment

8 + 3{x - 2[x + 5(x + 3)]}

= 8 + 3{x - 2(x + 5x + 15)}

= 8 + 3{x - 2(6x + 15)}

= 8 + 3(-11x - 30)

= 8 - 33x - 90

= -33x - 82

= 8 + 3{x - 2(x + 5x + 15)}

= 8 + 3{x - 2(6x + 15)}

= 8 + 3(-11x - 30)

= 8 - 33x - 90

= -33x - 82

Added 4/24/2015 7:00:12 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/25/2015 10:16:35 AM]

(y + z)3

Question

Updated 4/25/2015 5:39:19 AM

1 Answer/Comment

(y + z)3

= (y + z)*(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= (y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3)

= y^3 + 3y^2z + 3yz^2 + z^3

= (y + z)*(y + z)(y + z)

= (y^2 + 2yz + z^2)(y + z)

= (y^3 + 2y^2z + yz^2 + y^2z + 2yz^2 + z^3)

= y^3 + 3y^2z + 3yz^2 + z^3

Added 4/25/2015 2:59:59 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/25/2015 5:39:13 AM]

Factor this expression mn - 4m - 5n + 20

Question

Not Answered

Updated 5/1/2015 11:15:24 AM

1 Answer/Comment

mn - 4m - 5n + 20 = (m-5) (n-4)

Added 5/1/2015 11:15:24 AM

This answer has been confirmed as correct and helpful.

find the product of (6 - d)(d 2 - 5 + 3d)

Question

Not Answered

Updated 5/1/2015 11:24:46 AM

1 Answer/Comment

31,877,721

questions answered

There are no comments.